Bio-gel electrode based on dual-network crosslinking and preparation method and application thereof
By using a double network cross-linked structure of polyvinyl alcohol and gelatin in the bioelectrode, combined with the conductive properties of PEDOT:PSS and liquid metal gallium indium alloy, the problem of insufficient conductivity and stability of traditional bioelectrodes is solved, and efficient physiological electricity is achieved. Signal monitoring.
Patent Information
- Application Number
- CN202411664996.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-20
- Publication Date
- 2025-01-24
AI Technical Summary
Traditional biological electrodes lack electrical conductivity and stability when in contact with the skin, making it difficult to meet the long-term, high-fidelity physiological electrical signal monitoring needs.
Bio -gel electrodes based on polyvinyl alcohol and glee dual -network crosslinks are used to improve conductive performance through PEDOT: PSS and liquid metal alloy alloys, and use sodium borate as the cross -linked agent to form a dual network structure to enhance stability.
The biogeliness electrode with low impedance, excellent biocompatibility and self -healing ability is suitable for long -term, high -fidelity real physiological electrical signal monitoring, and improved signal quality and user experience.
Smart Images

Figure CN119350662A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to a biogel electrode based on double network crosslinking and a preparation method and application thereof, and in particular to a biogel electrode based on double network crosslinking of polyvinyl alcohol and gelatin and a preparation method and application thereof, belonging to the field of conductive hydrogel electrodes. Background Art
[0002] Bioelectric signals are generated along with the life activities of organisms, such as electromyography (EMG), electroencephalography (EEG), and electrocardiography (ECG). Although these signals are weak, usually fluctuating in the range of millivolts (mV) to microvolts (μV), they are crucial to revealing the health status and physiological activities of the human body. As a key sensing device, bioelectrodes play an indispensable role in many fields such as medical diagnosis, physiological research, neuroscience, and human-computer interaction. Its main responsibility is to capture and conduct these weak electrical signals for subsequent analysis and processing. However, traditional bioelectrodes face a series of challenges in practical applications, especially in terms of conductivity and stability when in contact with the skin. The state of the skin surface changes with time and environmental changes. For example, sweating or body movement will cause fluctuations in the skin-electrode contact impedance, thereby affecting the quality and reliability of the signal. In addition, the design of traditional electrodes is usually difficult to meet the requirements of cleaning and reuse, which further increases the complexity in actual operation.
[0003] In order to solve these problems, researchers began to pay attention to a new type of gel wet electrode. This type of electrode uses a gel material containing a conductive liquid to enhance contact with the skin surface, which can theoretically provide better conductivity. However, they still face the problems of insufficient mechanical strength and weak adhesion. In a dynamic environment, this unstable contact may lead to a decrease in signal quality. In addition, the physical property limitations of the gel itself, such as low tensile strength and poor viscoelasticity, make it difficult for these electrodes to be independently fixed on the skin surface, and they often need to be fixed with additional pressure-sensitive tape, which increases the complexity and inconvenience of the device. At present, most biogel electrodes on the market only show a single skin adhesion and lack the ability to adapt to different environmental factors. For example, unexpected adhesion to clothing during wearing can cause the electrode position to shift, which in turn affects the accuracy of the bioelectric signal. When the electrode needs to be repositioned, its original adhesion performance is often significantly reduced, which not only affects the user experience, but also increases the difficulty in practical applications.
[0004] Therefore, developing a new generation of gel electrode materials with higher conductivity, self-healing ability, and good biocompatibility, and designing a more compact and easy-to-use bioelectrode system has become an important research direction. By solving these problems, it is expected to promote the development of biomedical engineering technology. Summary of the invention
[0005] The technical problem solved by the present invention is: In order to overcome the shortcomings of the prior art, this study proposes a biogel electrode based on a double network cross-linking of polyvinyl alcohol and gelatin, and its preparation method and application. The electrode has excellent biocompatibility and low impedance. Its preparation process is simpler and easier to operate, and has high repeatability. The present invention successfully solves the defect that the contact impedance of traditional electrodes cannot remain stable for a long time, and exhibits the advantages of stable contact impedance, simple structure, good water retention and excellent biocompatibility, and is suitable for long-term, high-fidelity physiological electrical signal monitoring.
[0006] The technical solution of the present invention is:
[0007] A biogel electrode based on a double network cross-linking of polyvinyl alcohol and gelatin is a double network hydrogel, the raw materials of which include poly(3,4-ethylenedioxythiophene)-polystyrene sulfonic acid (PEDOT:PSS), polyvinyl alcohol, gelatin, liquid metal, sodium tetraborate and deionized water;
[0008] Taking the total mass of the raw materials of the biogel electrode as 100%, the mass percentage of each component is:
[0009] Poly(3,4-ethylenedioxythiophene)-polystyrene sulfonic acid 7.45%-7.68%
[0010] Polyvinyl alcohol 3.80%-3.82%
[0011] Gelatin 7.60%-7.76%
[0012] Liquid Metal 4.84-4.94%
[0013] Sodium tetraborate 3.51%-3.80%
[0014] Deionized water 72.18%-72.42%
[0015] Polyvinyl alcohol and gelatin are used as frameworks, PEDOT:PSS and liquid metal are used to reduce material impedance and provide conductive properties, and liquid metal can also be used with sodium tetraborate as a cross-linking agent.
[0016] A method for preparing a biogel electrode based on a double network cross-linking of polyvinyl alcohol and gelatin, comprising the following steps:
[0017] Step 1, preparing a precursor solution, specifically, dissolving a certain amount of polyvinyl alcohol and gelatin in deionized water, heating and stirring, adding liquid metal and PEDOT:PSS after they are completely dissolved, and performing ultrasonic dispersion to obtain a precursor solution;
[0018] Step 2, preparing a sodium tetraborate solution, the specific method is: heating and stirring a certain amount of sodium tetraborate and water at 50-60° C. to obtain a sodium tetraborate solution;
[0019] Step 3, pour the precursor solution obtained in step 1 into the mold, immerse it in the environment of sodium tetraborate solution, seal it with a sealing film, and let it stand at room temperature. After waiting for the complete cross-linking reaction, a biogel electrode with a double network cross-linking of polyvinyl alcohol and gelatin is obtained;
[0020] In the step 1, the pH value of the precursor solution is 7; the concentration of polyvinyl alcohol is 1.89-1.91 mmol / L, the concentration of gelatin is 0.63-0.65 mmol / L, the concentration of PEDOT:PSS is 0.2-0.44 mmol / L, the concentration of liquid metal is 1.34-1.36 mmol / L, the mixing temperature is 90-100°C, the ultrasonic dispersion power is 200-400 W, the ultrasonic dispersion time is 7-10 min, and the stirring time is 2-4 h.
[0021] In step 2, liquid metal gallium-indium alloy, the gallium mass fraction in the gallium-indium alloy is 75.5%, and the indium mass fraction is 24.5%. The sodium tetraborate is heated at a temperature of 50-60°C for a heating time of 0.5-1h, and the concentration of the sodium tetraborate solution is 10wt%;
[0022] In step 3, the precursor solution is immersed in the sodium tetraborate solution for 12-16 hours.
[0023] A biogel electrode prepared using a double network cross-linking technology of polyvinyl alcohol and gelatin, the application of which includes attaching the electrode to the surface of the skin as a sensor to detect bioelectric signals such as electrocardiogram, electromyography or electroencephalogram. The biogel electrode prepared using a double network cross-linking technology of polyvinyl alcohol and gelatin is attached to the skin as a sensor to measure bioelectric signals such as electrocardiogram, electromyography or electroencephalogram. The biogel electrode has excellent biocompatibility and conductivity, which can ensure that it remains gentle and non-irritating to the skin during long-term wear, while accurately capturing and transmitting bioelectric signals. Its unique double network cross-linking structure gives the electrode excellent stability and durability, allowing it to maintain excellent performance in various complex environments.
[0024] The present invention discloses a biogel electrode based on double network crosslinking of polyvinyl alcohol and gelatin, and a preparation method and application thereof, which belongs to the field of conductive hydrogel technology. The method uses polyvinyl alcohol, gelatin, liquid metal, poly(3,4-ethylenedioxythiophene)-polystyrene sulfonic acid (PEDOT:PSS) and the like as main raw materials. Among them, liquid metal gallium-indium alloy is a conductive filler, and sodium tetraborate is used as a crosslinking agent to obtain a bio-double network structure gel electrode with excellent conductivity, lower skin impedance and better self-healing. The hydrogel prepared by the present invention can be used as a bio-electrode patch for long-term, high-fidelity electrophysiological signal acquisition, such as electrocardiogram signals, electromyography signals, and electroencephalogram signals. In addition, the biogel electrode involved in the present invention has a simple preparation process, low cost, and good biocompatibility, and has great potential in large-scale production and promotion and application of electrode patches.
[0025] Due to the adoption of the above technical solution, the beneficial effects achieved by the present invention are:
[0026] (1) In the present invention, the conductivity of the electrode is optimized by stably dispersing PEDOT:PSS and liquid metal gallium indium alloy droplets in the hydrogel. PEDOT:PSS is a conductive polymer, and its distribution in the hydrogel can provide a continuous conductive path, thereby ensuring that the electrode has good conductivity. The liquid metal gallium indium alloy droplets further enhance the conductivity of the electrode due to their excellent conductive properties.
[0027] (2) In the present invention, polyvinyl alcohol and gelatin are used to construct a double network hydrogel structure, which not only gives the electrode good conductivity, but also significantly improves the biocompatibility and stability of the hydrogel through the synergistic effect of polyvinyl alcohol and gelatin. Polyvinyl alcohol, as a hydrophilic polymer material, can provide a good hydration environment and has good self-healing ability. In addition, the design of the double network structure also effectively prevents the swelling phenomenon of the hydrogel during long-term use, thereby ensuring that the electrode can work stably in the body for a long time.
[0028] (3) The low-impedance hydrogel electrode prepared by the present invention is suitable for monitoring the physiological electrical signals of muscles, heart and brain. By connecting to an external signal collector and a data processing module, ECG signals can be captured in real time. In addition, the direct contact between the gel electrode and the skin tissue ensures high signal-to-noise ratio signal sensing and excellent sensitivity. Thanks to its excellent conductivity, the electrode can fit tightly to various parts of the human body, including joints and curved skin areas, thus providing new possibilities for monitoring areas that are difficult to cover with traditional electrodes.
[0029] (4) The method of the biogel electrode of the double network crosslinking of polyvinyl alcohol and gelatin of the present invention, the field of data bioelectrode technology. The method uses polyvinyl alcohol, gelatin, liquid metal gallium indium alloy, PEDOT:PSS, sodium tetraborate as main raw materials, liquid metal as conductive component, and forms a double network structure through a crosslinking agent to obtain a biogel electrode with good conductivity and low skin contact impedance. The hydrogel prepared by the present invention can be used as a bioelectrode patch for electrocardiogram, electroencephalogram, and electromyography testing systems; in terms of signal acquisition, the electrode exhibits a good signal-to-noise ratio, good signal accuracy, lower impedance and excellent self-healing ability. In addition, the preparation method of the present invention is simple and suitable for large-scale production and promotion and application. BRIEF DESCRIPTION OF THE DRAWINGS
[0030] Figure 1 It is a schematic diagram of the process of preparing the biogel electrode of the present invention with a double network cross-linking of polyvinyl alcohol and gelatin;
[0031] Figure 2 This is a photo of the actual object of the biogel electrode with double network crosslinking of polyvinyl alcohol and gelatin of the present invention;
[0032] Figure 3 This is a real photo of the self-healing biogel electrode of the present invention with a double network cross-linking of polyvinyl alcohol and gelatin;
[0033] Figure 4 is a cross-sectional SEM image of a biogel electrode cross-linked with a double network of polyvinyl alcohol and gelatin according to the present invention;
[0034] Figure 5 It is an infrared spectrum of the biogel electrode of the present invention with double network cross-linking of polyvinyl alcohol and gelatin;
[0035] Figure 6 It is the impedance diagram of different contents (PEDOT:PSS, liquid metal) in the biogel electrode cross-linked by the double network of polyvinyl alcohol and gelatin of the present invention;
[0036] Figure 7 It is the skin interface impedance diagram of the biogel electrode cross-linked by the polyvinyl alcohol and gelatin double network of the present invention;
[0037] Figure 8 The invention discloses a biogel electrode electroencephalogram with a double network cross-linking of polyvinyl alcohol and gelatin;
[0038] Fig. 9 It is an electrocardiogram test diagram of a biogel electrode cross-linked with a double network of polyvinyl alcohol and gelatin according to the present invention;
[0039] Fig.10 It is a data diagram comparing the signal-to-noise ratio of the biogel electrode cross-linked by the polyvinyl alcohol and gelatin double network of the present invention and the commercial electrode;
[0040] Fig.11 This is an electromyographic test diagram of a biogel electrode cross-linked with a double network of polyvinyl alcohol and gelatin according to the present invention. DETAILED DESCRIPTION
[0041] The present invention is further described below in conjunction with the accompanying drawings and specific embodiments, but the protection scope of the present invention is not limited thereto.
[0042] like Figure 1 As shown, a method for preparing a biogel electrode based on a double network cross-linking of polyvinyl alcohol and gelatin comprises the following steps:
[0043] Step 1: Prepare the precursor solution. The specific method is: dissolve a certain amount of polyvinyl alcohol and gelatin in deionized water and heat and stir. After they are completely dissolved, add liquid metal and PEDOT:PSS and perform ultrasonic dispersion to obtain the precursor solution:
[0044] Step 2, preparing a sodium tetraborate solution, specifically, heating and stirring a certain amount of sodium tetraborate and water at 50° C. to obtain a sodium tetraborate solution;
[0045] Step 3, pour the precursor solution obtained in step 1 into the mold, immerse it in the environment of sodium tetraborate solution, seal it with a sealing film, and let it stand at room temperature. After waiting for the complete cross-linking reaction, a biogel electrode with a double network cross-linking of polyvinyl alcohol and gelatin is obtained;
[0046] Example 1
[0047] A method for preparing a biogel electrode based on a double network cross-linking of polyvinyl alcohol and gelatin comprises the following steps:
[0048] Step 1, weigh 1g polyvinyl alcohol, 2g gelatin, 2mL PEDOT:PSS, add to 10mL deionized water, heat at 90°C and stir with a magnetic stirrer for 2h-4h, add 1.3g liquid metal gallium-indium alloy to the solution after complete dissolution, disperse for 6-8min at an ultrasonic power of 300w, and obtain a precursor solution; wherein the mass fraction of gallium in the gallium-indium alloy is 75.5%, and the mass fraction of indium is 24.5%; the solution concentration is 0.012mmol / L, and the pH value is 7;
[0049] Step 2, weigh 1g of sodium tetraborate and dissolve it in 9ml of deionized water, heat and stir at 50°C for 1h-2h, and after it is completely dissolved, a sodium tetraborate solution with a concentration of (10wt%) can be obtained;
[0050] Step 3, add 0.15 ml of the sodium tetraborate solution obtained in step 2 to the mold surface, then add 0.5 ml of the precursor solution prepared in step 1 to the mold, and then add 0.15 ml of the sodium tetraborate solution again. The mold is sealed and stored at room temperature for 16 hours to obtain a biogel electrode with a double network cross-linked of polyvinyl alcohol and gelatin, which is named 10PEDOT:PSS_LM (10%).
[0051] Example 2
[0052] The difference from Example 1 is that the mass of the liquid metal gallium-indium alloy added in step 1 is 0.4 g, and it is named PEDOT:PSS-0.4LM hydrogel;
[0053] Example 3
[0054] The difference from Example 1 is that the mass of the liquid metal gallium-indium alloy added in step 1 is 0.6 g, and it is named PEDOT:PSS-0.6LM hydrogel;
[0055] Example 4
[0056] The difference from Example 1 is that the mass of the liquid metal gallium-indium alloy added in step 1 is 0.8 g, and it is named PEDOT:PSS-0.8LM hydrogel;
[0057] Example 5
[0058] The difference from Example 1 is that the mass of the liquid metal gallium-indium alloy added in step 1 is 1.3 g, and then 0.75 mL of the precursor solution is added, which is named 15PEDOT:PSS-LM (10%) hydrogel.
[0059] Comparative Example
[0060] The difference from Example 1 is that the liquid metal gallium-indium alloy is added in step 1, but no liquid metal gallium-indium alloy is added in this Example 2, which is named PEDOT:PSS-Non-LM hydrogel;
[0061] Figure 2 a is a photo of the PEDOT:PSS-Non-LM gel electrode in the comparative example. Figure 2 b is a real photo of Example 5 (10%), Figure 2 c is a picture of actual human skin in Example 5, Figure 2 The left sample of d is a biogel electrode with a double network cross-link of polyvinyl alcohol and gelatin containing liquid metal, and the right sample is a biogel electrode with a double network cross-link of polyvinyl alcohol and gelatin without liquid metal;
[0062] Figure 3The actual self-healing process of the hydrogel in Example 5 is demonstrated. It is attributed to the two water-soluble polymer materials, polyvinyl alcohol and gelatin. They can build a network structure through hydrogen bonding interactions. When the hydrogel is damaged by external forces, these hydrogen bonds can reconnect, thereby restoring the hydrogel to its original state. In addition, the introduction of PEDOT:PSS increases the hydrogen bonding content of the hydrogel, thereby further enhancing the self-healing ability of the hydrogel.
[0063] Figure 4 This is a scanning electron microscope image of a biogel electrode based on a double network crosslinking of polyvinyl alcohol and gelatin. From the image, it can be seen that the material has a distinct porous structure. These pores may be due to the cavities left after the evaporation of water in the hydrogel or the formation of ice crystals.
[0064] The flexible circuit combined with hydrogel can read, process and transmit the electrocardiogram, electromyography and electroencephalogram. The PEDOT on the hydrogel electrode is mainly composed of the sulfonic acid group (-SO3 - ), these negatively charged sulfonic acid groups can interact with the positively charged sites on the skin surface, thereby enhancing adhesion. When the precursor solution and sodium tetraborate hydrogel are prepared, the improvement in conductivity is mainly attributed to the presence of PEDOT:PSS. Specifically, the PEDOT part (poly (3,4-ethylenedioxythiophene)) in PEDOT:PSS is a conductive polymer, while the PSS part (poly (styrene sulfonic acid)) acts as a stabilizer and dopant. Specifically, PEDOT is usually connected to the skin through the sulfonic acid groups (-SO3 - ) doping, which delocalizes the π electrons in the PEDOT molecule and forms a conductive path. This doping process makes the π electrons on the thiophene ring in PEDOT more mobile, thereby improving conductivity;
[0065] Figure 5 The infrared spectra of three different hydrogels (Example 1, Example 5, Comparative Example) are shown. The peak near 3000 cm-1 may be related to the CH bond, the peak near 3300-3500 cm-1 may be related to the NH bond, the peak near 3200-3600 cm-1 may be related to the OH bond, the peak near 1650-1800 cm-1 may be related to the C=O bond, and the peak near 1600-1680 cm-1 may be related to the C=C bond. As can be seen from the figure, at a wave number of 3500 cm-1 -1 There is an obvious absorption peak around 2900 cm-1. The chemical bond corresponding to this peak is mainly OH stretching vibration, indicating that the sample contains a large number of hydroxyl (OH) groups, indicating that as the content of liquid metal and PEDOT:PSS increases, hydrogen bonds increase. In addition, at a wave number of about 2900 cm-1 -1There is also a smaller but clearly visible absorption peak at the position of , which is usually associated with CH stretching vibration, suggesting the presence of alkane chain structures such as methyl (CH3) or methylene (CH2).
[0066] Figure 6 a is the biogel electrodes of 15PEDOT:PSS_LM (10%), 10PEDOT:PSS_LM (10%), and PEDOT:PSS-Non-LM obtained in Example 1 of the present invention, comparative example, and Example 5, and impedance test was performed by using CHI760E electrochemical work of Shanghai Chenhua Co., Ltd. The test frequency was 0.1Hz-100000Hz. Figure 6 a It can be seen that as the content of liquid metal and PEDOT:PSS increases, the impedance becomes lower, that is, the conductivity increases. Figure 6 b Shanghai Chenhua Co., Ltd. CHI760E electrochemical workstation was used to test the impedance of the biogel electrode made of polyvinyl alcohol and gelatin double network crosslinked with different contents of liquid metal gallium indium alloy. Figure 6 b It can be seen that with the increase of liquid metal and PEDOT:PSS content, the impedance decreases. Figure 6 It can be seen that the increase of liquid metal also reduces the skin interface impedance of the hydrogel, further improving the accuracy and signal-to-noise ratio of physiological electrical signals.
[0067] Figure 7 The skin interface impedance was tested by using a double-network cross-linked biogel electrode made of polyvinyl alcohol and gelatin prepared with different contents of liquid metal gallium-indium alloy. Figure 7 a is a schematic diagram of the test method. Figure 7 b is a graph showing the skin interface impedance test of Example 5 and the comparative example. It can be seen from the graph that as the amount of liquid metal increases, the impedance decreases.
[0068] Figure 8 This is an EEG test diagram of the biogel electrode cross-linked with a double network of polyvinyl alcohol and gelatin of the present invention. It can be seen from the figure that during the blinking process, the peak value of the EEG characteristic signal of the biogel electrode cross-linked with a double network of polyvinyl alcohol and gelatin with liquid metal added is significantly improved, showing a stronger signal response. This shows that the introduction of liquid metal significantly enhances the signal conduction ability of the electrode, making the detection of EEG signals more sensitive and accurate. In addition, by comparing the test results of electrodes with different liquid metal contents, it can be found that with the increase of liquid metal content, the peak value of the EEG signal gradually increases, and the signal quality is further improved. Fig. 9 This is a schematic diagram of a gelatin double network cross-linked biogel electrode and a commercial ECG. Fig. 9 a is the gelatin double network cross-linked biogel electrode of this invention, Fig. 9b is a commercial electrode ECG diagram, the waveform and interval represent the electrophysiological process of different parts of the heart, mainly P wave (representing the depolarization of the atrium), QRS complex wave (Q wave: visible in some cases, representing the initial depolarization of the ventricular septum, R wave: representing the depolarization of the right ventricle, S wave: representing the depolarization of the left ventricle), T wave (representing the repolarization of the ventricle), U wave (sometimes visible, may be related to the flow of potassium ions in myocardial cells). Each interval represents something different. The PR period is the time from the start of the P wave to the start of the QRS complex, reflecting the process from the beginning of atrial depolarization to the beginning of ventricular depolarization. The QT period is the time from the start of the QRS complex to the end of the T wave, reflecting the total time of ventricular depolarization and repolarization. The RR period is the distance between two adjacent R waves, reflecting the heartbeat cycle. An example of using the biogel electrode of the present invention to perform electrocardiogram (ECG) measurement is shown. In general, whether using Example 6 or a commercial electrode, the ECG record shows clear QRS waves, QT waves, RR waves and PR waves. This shows that both electrodes can effectively capture the signals of cardiac electrophysiological activity. In addition, the signal-to-noise ratio is one of the important indicators to measure the performance of the electrode, which reflects the clarity and accuracy of the signal captured by the electrode.
[0069] Fig.10 It can be seen that the signal-to-noise ratio of the biogel electrode of the present invention is 35.24 dB, and the signal-to-noise ratio of the commercial electrode is 34.92 dB, that is, the biogel electrode of the present invention has an obvious advantage in signal-to-noise ratio.
[0070] Fig.11 Electromyography measures the changes in potential generated when muscles contract. Using the electromyography acquisition system (OpenBCI), it can be seen from the figure that each fist clenching is accompanied by obvious potential fluctuations, and these fluctuations have good repeatability and consistency. The arm was repeatedly clenched four times in real time. Before and after each fist clenching, the signal is relatively stable, indicating that the muscles are in a relaxed state, and the potential amplitude during fist clenching increases significantly.
[0071] In summary, this study developed a biogel electrode with good conductivity and a double network cross-linked polyvinyl alcohol and gelatin. The biogel electrode can achieve long-term. In addition, the biogel electrode exhibits excellent biocompatibility and long-term stable signal acquisition performance, which provides a guarantee for the continuous stability of ECG, EMG and EEG signal acquisition systems. The biogel electrode with good conductivity obtained by the preparation method proposed in this study, and it shows good bioadaptability, has excellent signal acquisition performance, and is compatible with existing hydrogel signal acquisition equipment.
[0072] Although the present invention has been described in detail with reference to the accompanying drawings and in combination with specific embodiments, it should be understood that the present invention is not limited to the embodiments. Without departing from the spirit and essence of the present invention, ordinary technicians in the relevant field can make various forms of equivalent transformations or substitutions to the above embodiments, and all these changes and substitutions should be included in the scope of protection of the claims of the present invention. Any changes or substitutions that can be thought of by any technician in this technical field under the technical enlightenment disclosed by the present invention should be covered within the scope of protection of the present invention.
Claims
1. A biogel electrode based on a double network cross-linking of polyvinyl alcohol and gelatin, characterized in that: The raw materials of the biogel electrode include poly(3,4-ethylenedioxythiophene)-polystyrene sulfonic acid, polyvinyl alcohol, gelatin, liquid metal, sodium tetraborate and deionized water; Taking the total mass of the raw materials of the biogel electrode as 100%, the mass percentage of each component is: Poly(3,4-ethylenedioxythiophene)-polystyrene sulfonic acid 7.45%-7.68% Polyvinyl alcohol 3.80%-3.82% Gelatin 7.60%-7.76% Liquid Metal 4.84-4.94% Sodium tetraborate 3.51%-3.80% Deionized water 72.18%-72.42%.
2. A method for preparing a biogel electrode based on a double network crosslinking of polyvinyl alcohol and gelatin, characterized in that the steps include: Step 1, preparing a precursor solution; Step 2, preparing a sodium tetraborate solution; Step 3, pouring the precursor solution obtained in step 1 into the mold and soaking it in the sodium tetraborate solution prepared in step 2 to cause a cross-linking reaction. After the reaction is completed, a biogel electrode with a double network cross-linking of polyvinyl alcohol and gelatin is obtained.
3. The method for preparing a biogel electrode based on double network crosslinking of polyvinyl alcohol and gelatin according to claim 2, characterized in that: In step 1, the method for preparing the precursor solution is: dissolving polyvinyl alcohol and gelatin in deionized water, heating and stirring, adding liquid metal and poly(3,4-ethylenedioxythiophene)-polystyrene sulfonic acid after they are completely dissolved, and performing ultrasonic dispersion to obtain a precursor solution.
4. The method for preparing a biogel electrode based on a double network crosslinking of polyvinyl alcohol and gelatin according to claim 2, characterized in that: In step 2, the method for preparing the sodium tetraborate solution is: heating and stirring the sodium tetraborate and water at 50-60° C. to obtain the sodium tetraborate solution.
5. The method for preparing a biogel electrode based on double network crosslinking of polyvinyl alcohol and gelatin according to claim 3, characterized in that: In the step 1, the pH value of the precursor solution is 7; the concentration of polyvinyl alcohol is 1.89-1.91 mmol / L, the concentration of gelatin is 0.63-0.65 mmol / L, the concentration of PEDOT:PSS is 0.2-0.44 mmol / L, the concentration of liquid metal is 1.34-1.36 mmol / L, the mixing temperature is 90-100°C, the ultrasonic dispersion power is 200-400 W, the ultrasonic dispersion time is 7-10 min, and the stirring time is 2-4 h.
6. The method for preparing a biogel electrode based on a double network cross-linking of polyvinyl alcohol and gelatin according to claim 4, characterized in that: In the step 2, liquid metal gallium-indium alloy is prepared, wherein the mass fraction of gallium in the gallium-indium alloy is 75.5% and the mass fraction of indium is 24.5%.
7. The method for preparing a biogel electrode based on double network crosslinking of polyvinyl alcohol and gelatin according to claim 4, characterized in that: In step 2, the sodium tetraborate heating time is 0.5-1h, and the concentration of the sodium tetraborate solution is 10wt%.
8. The method for preparing a biogel electrode based on double network crosslinking of polyvinyl alcohol and gelatin according to claim 2, characterized in that: In step 3, the precursor solution is immersed in the sodium tetraborate solution for 12-16 hours.
9. An application of a biogel electrode based on a double network cross-linking of polyvinyl alcohol and gelatin, characterized in that: The biogel electrode based on double network cross-linking of polyvinyl alcohol and gelatin is attached to the skin surface and used as a sensor to detect bioelectric signals such as electrocardiogram, electromyography or electroencephalogram.
Citation Information
Patent Citations
Thermosensitive biogel electrode and preparation method and application thereof
CN117487200A
Cited By
Preparation method and application of flexible gel electrode for electroencephalogram monitoring
CN120304838A